OCCUPATIONAL SAFETY CHALLENGES IN THE CONSTRUCTION INDUSTRY OF SINDH, PAKISTAN: AN ANALYSIS OF ACCIDENT DATA AND SAFETY IMPLEMENTATION - Mujtaba Hassan; Rabia Soomro; Sohail Ahmed; Atiqa Aslam; Touqeer Ali Rind (Spectrum of Engineering Sciences, 2025)
This study investigates occupational safety in the construction industry of Sindh, Pakistan, highlighting the persistent issue of workplace accidents despite existing safety regulations. A review of the literature reveals a gap in empirical data focusing on accident count and state of safety practices in the construction industry of Sindh. The objectives of this research are to identify the frequency of occupational accidents and assess the level of implementation of safety measures in targeted construction companies. A quantitative research method was adopted for this research. The data was collected through a structured questionnaire, distributed among 386 construction companies in Sindh. The data collection process involved direct contact with safety managers and supervisors to ensure accurate reporting of accident statistics and safety practices. The data analysis was performed using SPSS, employing descriptive statistics to evaluate safety measure implementation and accident frequencies. The results indicate a total of 894 accidents over the past five years in 386 construction companies of Sindh, comprising 79 fatal, 231 non-fatal, and 584 property damage incidents. Key findings highlight inadequate safety training, insufficient personal protective equipment, and a prevalent culture of risk-taking. The study underscores the need for stringent safety protocols, improved training programs, and regulatory enforcement. This research emphasizes the urgent need for systematic safety interventions in Sindh’s construction industry to foster a safer working environment.